Localização e avaliação da qualidade do aplicativo de saúde móvel Surewash Pocket® - Baggio, Érica (2020)
infections related to health care are adverse events that threaten patient safety and are considered a serious public health problem globally, both due to the high frequency and associated morbidity and mortality. With regard to measures to prevent and control these infections, hand hygiene is considered the most effective and least expensive practice. However, despite the recommendations for adhering to hand hygiene being widely disseminated by government health agencies, many health professionals continue not to adopt this measure in the care routine as recommended. In view of this, the World Health Organization released the multimodal strategy, composed of five key components, to improve adherence to hand hygiene of health professionals. With regard to the second component of this strategy, which refers to the education and training of health professionals, active and innovative learning has been recommended during education with health workers. In this context, the combination of active and hybrid learning with mobile technologies, such as mobile health apps (mHealth apps), can represent a promising strategy for planning new ways of learning and teaching. Therefore, these tools, when well elaborated and used, can contribute as an adjunct to continuing health education. In the search for mobile applications related to hand hygiene for health professionals in virtual stores, no national productions were found, however six applications from other nationalities were identified, and one of these, called SureWash Pocket®, presented a clear educational methodology and quality rating good to excellent. General objective: perform the localization for Brazilian Portuguese and the quality assessment of the mobile health application SureWash Pocket®. Material and Methods: this is a study with methodological design and quantitative approach. The development of this study consists of two distinct moments. The first moment refers to the process of locating the textual interface of the mobile health application SureWash Pocket® for the Brazilian Portuguese language, which was carried out following six steps: 1) Permission to locate the software; 2) Two independent translations from the source language to the target language; 3) Synthesis of translations; 4) Evaluation of the validity of the textual interface by a Committee of Expert Judges; 5) Reverse translation; and 6) Publication in online stores. In the second moment, ten health professionals assessed the quality of the application by means of the Application Evaluation Scale (EAA) Application User Version. In this study, a cut-off point of 3 was established, according to the minimum acceptability value established by the scale. Results: a review was carried out in online stores of mobile applications on hand hygiene for health professionals, which pointed out two applications, SureWash Pocket® and Give Me 5, as tools that can be used as adjuvants in the process of continuing education in health on hand hygiene to enhance the expected health results. It is worth mentioning that SureWash Pocket® was the only application that achieved a good quality rating in all dimensions evaluated and presented a clear educational methodology. Thus, a partnership was made with the developer of this application to localize the textual interface for the Brazilian Portuguese language. The translation analysis was performed by ten expert judges and resulted in changes related mainly to semantic equivalence. Regarding the quality assessment of the localized application, the average EAA score for the application quality ratings domain was 4.11 (SD 0.43), classified as good to excellent quality by health professionals. The subjective quality of the application was the section with the lowest average score (mean 3.27; SD 0.83), which ranged from bad to good. The application-specific section, which represents the perceived impact of using the application on health behavior change, averaged 3.93, with high variability (SD 1.35). Conclusion: the process of locating the mobile health application suggests that the Brazilian Portuguese version of SureWash Pocket® can be considered valid, from the point of view of the textual interface. The average quality assessment of the application located by health professionals showed good to acceptable quality in all sections. Future studies should focus on evaluating the software through clinical trial intervention with the target audience, in order to highlight the user's most striking experiences regarding the interaction with the digital device.